Market study to achieve the export of baby clothes made from cotton native - Montes López, Edwin Marcelo (2018)
The objective of the present study was to elaborate a market study for the export of baby clothes made from cotton of the region of lambayeque, this study is structured defining the characteristics of the product and its participation in the world market, achieving with it An analysis of supply and demand, allowing in the first stage to identify three interesting markets for our product, such as the United Kingdom, France and Mexico, also allowing to identify china, bangladesh and india as the top three exporters of cotton baby clothing. To determine the country that would constitute our potential demand, in a second stage a quantitative and qualitative analysis was developed between the three interesting markets So it was concluded that at present the craftsmen of the region do not export textile handcraft products based on native cotton. Finally, it is recommended to establish a joint partnership between the regional management of foreign trade and tourism, the center of technological innovation and the NGOs involved, in implementing a training process for new potential markets.